Making it work: The mixed embeddedness of immigrant entrepreneurs in New Zealand - Trudie Cain; Paul Spoonley (Institute for the Study of Labor (IZA), 2013)
In seeking economic immigrants, especially those who are skilled, entrepreneurial and with capital to invest, a settler country such as New Zealand has assumed that national and city labour markets/economies will gain by adding to the human capital pool as well as creating new 'economic' activities of various sorts. Economic participation, both as labour but also as typically small business owners, often reflects the nature of mixed embeddedness (Kloosterman and Rath 2003) and especially the relational embeddedness (Portes, cited in, Vertovec 2009) of particular immigrant groups. This is most apparent in relation to social and economic networks, the deployment of human capital, immigrant engagement strategies and transnational activities. Using the concept of mixed embeddedness, this paper examines the strategies and outcomes for migrant entrepreneurs from the People's Republic of China, the Republic of Korea, India, South Africa and the United Kingdom, drawing upon a largely qualitative analysis of immigrant employers from these groups.
Keywords: J15; J24; J39; 330; migration; relational embeddedness; structural embeddedness; mixed embeddedness; New Zealand; immigrant entrepreneurs